Evaluation of aspartate aminotransferase to platelet ratio index and fibrosis 4 scores for hepatic fibrosis assessment compared with transient elastography in chronic hepatitis C patients - Sripongpun, P; Tangkijvanich, P; Chotiyaputta, W; Charatcharoenwitthaya, P; Chaiteerakij, R; Treeprasertsuk, S; Bunchorntavakul, C; Sobhonslidsuk, A; Leerapun, A; Khemnark, S; Poovorawan, K; Siramolpiwat, S; et al. (Wiley, 2019)
Background and Aim: Fibrotic stage (FS) assessment is essential in chronic hepatitis C treatment cascade. Liver stiffness measurement (LSM) using transient elastography (TE) is reliable and correlated with liver biopsy. However, TE may not be widely available. This study aimed to evaluate the diagnostic performances of aspartate aminotransferase to platelet ratio index (APRI) and fibrosis 4 (FIB‐4) scores compared with TE.